2016
DOI: 10.3109/0284186x.2015.1125014
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in breast cancer incidence and mortality in Estonia: Transition to the west

Abstract: Background The aim of this study was to examine breast cancer (BC) incidence and mortality trends in Estonia during recent decades and to compare the pattern of these trends with other selected European countries and regions. We attempt to explain the findings in relation to changes in Estonian society and healthcare system. Methods BC incidence (1985-2012) and mortality (1985-2013) data for Estonia were obtained from the Estonian Cancer Registry and Statistics Estonia. Data for selected European countries we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In multivariate analysis, RT utilization was the highest among women aged 50–59 and the difference from older and younger age groups was borderline significant. It has been reported previously that mortality from BC among patients aged 50–59 in Estonia has significantly declined since 2000, while it did not decrease among women aged ≥ 60 over the same time period [ 2 ]. Whereas these trends are consistent with screening activities, as women aged 50–59 have been the target age group for organized mammography screening since 2004 [ 20 ], the impact of RT in combination with other therapies can be considered as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multivariate analysis, RT utilization was the highest among women aged 50–59 and the difference from older and younger age groups was borderline significant. It has been reported previously that mortality from BC among patients aged 50–59 in Estonia has significantly declined since 2000, while it did not decrease among women aged ≥ 60 over the same time period [ 2 ]. Whereas these trends are consistent with screening activities, as women aged 50–59 have been the target age group for organized mammography screening since 2004 [ 20 ], the impact of RT in combination with other therapies can be considered as well.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) is a major health burden among women worldwide as well as in Estonia. Although overall BC incidence has increased in Estonia [ 1 ], mortality from BC has decreased steadily since 2000 [ 2 ]. However, there’s still a survival gap between Estonia and more developed countries [ 3 ], despite rapid increase observed since 1990s, particularly for locally/regionally spread cancers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, however, this belief is only a myth as around 45% of the cases and 55% of deaths due to breast cancer occur in low- and middle-income countries, according to recent estimates [ 11 , 26 ]. Adoption of “western lifestyle” is largely implied in increasing the incidence and burden of breast cancer in low- and middle-income countries [ 11 , 27 ].…”
Section: Breast Cancer: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Previous studies of BC trends in Estonia have indicated that in parallel with continuous incidence increase, mortality started to slowly decrease in the second half of the 1990s. 15 This was accompanied by an increase in relative survival. 16 , 17 Declining mortality together with consistent survival increases in Europe have been contributed to increasing proportions of women being diagnosed at an earlier stage, enabling more effective treatment.…”
Section: Introductionmentioning
confidence: 98%